Au nanoparticles decorated polypyrrole-carbon black/g-C3N4 nanocomposite as ultrafast and efficient visible light photocatalyst. (January 2022) - Faisal, M.; Rashed, Md A.; Ahmed, Jahir; Alsaiari, Mabkhoot; Jalalah, Mohammed; Alsareii, S.A.; Harraz, Farid A.
Abstract: Modification and bandgap engineering are proposed to be extremely significant in improving the photocatalytic activity of novel photocatalysts. The current research focused on the fabrication of ultrafast and efficient visible light-responsive ternary photocatalyst containing g-C3 N4 nanostructures in conjugation with polypyrrole doped carbon black (PPy-C) and gold (Au) nanoparticles by highly effectual, simple, and straightforward methodology. Various analytical techniques like XRD, FESEM, TEM, XPS, FTIR, and UV–Vis spectroscopy were applied for characterization purposes. The XRD and XPS results confirmed the successful creation of a nanocomposite framework among Au, PPy-C and g-C3 N4 . The TEM images revealed that bare g-C3 N4 holds sheets or layered graphitic structure with sizes ranging from 100 to 300 nm. The sponge-like PPy-C network intermingled perfectly with g-C3 N4 sheets along with homogeneously distributed 5–15 nm Au nanoparticles. The band gap energy (Eg ) for bare g-C3 N4, PPy-C/g-C3 N4 and Au@PPy-C/g-C3 N4 nanocomposites were found to be 2.74, 2.68, and 2.60 eV, respectively. The photocatalytic activity for all newly designed photocatalysts have been assessed during the degradation of insecticide Imidacloprid and methylene blue (MB) dye, where Au@PPy-C/C3 N4 was found to be extremely efficient with ultrafast removal of both imidacloprid and MB in just 25 min of visible light irradiation. It was revealed that the Au@PPy-C/g-C3 N4 ternary photocatalyst removed 96.0% of target analyte imidacloprid, which is ⁓ 2.91 times more efficient than bare g-C3 N4 in treating imidacloprid. This report provides a distinctly promising, highly effectual and straightforward route to destruct extremely toxic and notorious pollutants and opens a new gateway in the present challenging scenario of environmental concerns. Graphical abstract: Image 1 Highlights: A novel Au@PPy-C/g-C3 N4 nanocomposite photocatalyst via a simple pyrolysis technique. Ultrafast photodegradation of imidacloprid insecticide under visible light. Enhanced light absorption with efficient charge carrier separation is detected. The k value of active photocatalyst is 291% larger than the undoped photocatalyst. The Au@PPy-C/g-C3 N4 photocatalyst exhibits excellent stability and reusability.